ANALISIS BUDAYA SIRI’ DALAM KAJIAN SEMANTIK PADA MASYARAKAT BUGIS DI MARABATUAN KECAMATAN PULAU SEMBILAN KABUPATEN KOTABARU - Normasunah Normasunah (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2019)
Formulation of the problem in this study (1) What is the appearance of siri culture in the Bugis community in Marabatuan Pulau Sembilan District Kotabaru Regency (2) How is the meaning of culture for the Bugis community in Marabatuan Pulau Sembilan District Kotabaru Regency. The objectives of this research are (1) To describe the form of siri culture in the Bugis community in Marabatuan, Pulau Sembilan District, Kotabaru Regency. (2) Describe the meaning of siri culture for the Bugis community in Marabatuan, Pulau Sembilan District, Kotabaru Regency. The method used in this research is descriptive qualitative research method that is to describe objectively and actual things related to siri culture. Data collection techniques include (1) observation (2) interviews and (3) documentation. The results of this study indicate that the form of siri 'explained by the Bugis community in Marabatuan is a social problem, such as silariang, infidelity, life competition, public officials, dui pappenre and hajj, this can be seen in everyday life where siri 'it plays a role and dominates in it and influences the actions of someone who is involved in the case of siri', as for the actions of someone who is humiliated, is highly dependent on the conditions of interdependence, while the meaning of siri 'is shame, honor, dignity and self-respect which is highly guarded and is the identity of a Bugis, a violation of siri 'can cause prolonged conflict and even murder. However, in the research site there has never been a case of murder of siri 'someone who was injured, however this culture of shame is still respected, obeyed and remembered by the Bugis community in Marabatuan. Keywords: Siri Culture ', Semantics, Bugis Society.